2021
DOI: 10.1111/tri.13865
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the causes of the high incidence of delayed graft function after kidney transplantation in Brazil: a multicenter study

Abstract: This retrospective multicenter (n = 18) cohort study evaluated the incidence, risk factors, and the impact of delayed graft function (DGF) on 1year kidney transplant (KT) outcomes. Of 3992 deceased donor KT performed in 2014-2015, the incidence of DGF was 54%, ranging from 29.9% to 87.7% among centers. Risk factors ( lower-bound-95%CI OR upper-bound-95% CI ) were male gender ( 1.066 1.249 1.463 ), diabetic kidney disease ( 1.053 1.296 1.595 ), time on dialysis ( 1.005 1.007 1.009 ), retransplantation ( 1.035 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 30 publications
3
22
0
4
Order By: Relevance
“…Two-thirds of the recipients in the present study developed DGF by the definition adopted in the present study. This frequency is similar to the one found in the Brazilian multicenter study ( 7 ) and to previous monocentric Brazilian studies ( 8 , 9 ) but is much higher than that reported in other national registries ( 28 , 29 ). Importantly, we observed a high incidence of acute rejection and borderline findings in the surveillance biopsies, which is in line with previous reports ( 8 , 9 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Two-thirds of the recipients in the present study developed DGF by the definition adopted in the present study. This frequency is similar to the one found in the Brazilian multicenter study ( 7 ) and to previous monocentric Brazilian studies ( 8 , 9 ) but is much higher than that reported in other national registries ( 28 , 29 ). Importantly, we observed a high incidence of acute rejection and borderline findings in the surveillance biopsies, which is in line with previous reports ( 8 , 9 ).…”
Section: Discussionsupporting
confidence: 90%
“…It varies from around one-fourth to approximately two-thirds of kidney transplants from brain-dead deceased donors ( 26 29 ). In Brazil, for reasons that are not entirely understood, the reported incidence of DGF is consistently higher compared to other registries ( 7 - 9 ). In a recently published large Brazilian multicenter study, we found a high incidence of DGF and concluded that late referral and poor donor maintenance account for the high overall incidence while variability in donor and recipient selection, organ preservation method, and type of antibody induction may account for the wide variation observed among centers ( 7 ).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…These variables included recipient age, donor age, mean TAC levels (considering five TAC levels before the protocol biopsy), induction therapy (basiliximab vs. thymoglobulin), expanded criteria donor, delayed graft function, defined as the need for dialysis in the first week post-transplantation, cold ischemia time, and transfusions prior to KT. These clinical variables have been related to acute graft inflammation [ 27 , 28 , 29 , 30 , 31 ]. The Hosmer–Lemeshow goodness of fit was the principal criterion for selection of the final models.…”
Section: Methodsmentioning
confidence: 99%
“…Between 54 and 71% of recipients of deceased donor kidney transplants develop delayed graft function (DGF). This high incidence is a consequence of relatively late donor referral, inadequate donor maintenance and long cold ischemia times (5).…”
Section: Transplant Numbers and Outcomesmentioning
confidence: 99%